2021
DOI: 10.3389/fphar.2021.690538
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biochemical Study of Anti-Dermal Fibroblast Replicative Senescence Potential of Panax Notoginseng Oligosaccharides

Abstract: Dermal fibroblast replicative senescence that often occurs in aging skin is characterized by loss of cell proliferative capacity, cell cycle arrest, decreased cell elongation, and decreased synthesis of dermal extracellular matrix (ECM) components. Although Panax notoginseng is known for its effectiveness in alleviating many age-related degenerative diseases, few studies have evaluated P. notoginseng components for efficacy or mechanisms of action in delaying cell replicative senescence. In this study, P. noto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zhai et al found that Panax notoginseng oligosaccharides isolated from Panax notoginseng could reverse fibroblast replicative senescence by promoting fibroblast proliferation, migration and CoL-I production. 35 Panax notoginseng saponins can protect tumor necrosis factor-α-induced osteoarthritis rat chondrocytes from aging and apoptosis by regulating the PI3K-AKT-mTOR pathway, thereby delaying the destruction of cartilage by osteoarthritis. 36 Moreover, Panax notoginseng polysaccharides can significantly prolong the average lifespan of wildtype Caenorhabditis elegans and may increase the survival rate of wildtype Caenorhabditis elegans under heat stress by increasing the activities of SOD and CAT and reducing the content of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Zhai et al found that Panax notoginseng oligosaccharides isolated from Panax notoginseng could reverse fibroblast replicative senescence by promoting fibroblast proliferation, migration and CoL-I production. 35 Panax notoginseng saponins can protect tumor necrosis factor-α-induced osteoarthritis rat chondrocytes from aging and apoptosis by regulating the PI3K-AKT-mTOR pathway, thereby delaying the destruction of cartilage by osteoarthritis. 36 Moreover, Panax notoginseng polysaccharides can significantly prolong the average lifespan of wildtype Caenorhabditis elegans and may increase the survival rate of wildtype Caenorhabditis elegans under heat stress by increasing the activities of SOD and CAT and reducing the content of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Kr-h1 (Santa Cruz Biotechnology, Santa Cruz, USA). Next, the membranes were incubated with appropriate secondary antibodies (Li-Cor, Lincoln, NE, USA) for 1 h at room temperature ( 31 ). Finally, chemiluminescence-based visualization and analysis of protein bands were conducted using a FluorChem imaging system (ProteinSimple, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, fibroblasts are present throughout the matrix and connective tissue of the body. Therefore, NIH-3T3 cell line has been previously used for studying the regulation of fibrillar collagen synthesis, cellular cytotoxicity, genotoxicity, inhibition of UV-induced skin photoaging, inhibition of MMPs, etc., of tested compounds or topical formulations [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Briefly, NIH/3T3 cell line were cultured in DMEM culture medium with 10.0% newborn calf serum, and 1.0% antibiotic–antimycotic (100×).…”
Section: Methodsmentioning
confidence: 99%